Sylwia Wojciechowska. Conceptual Metonymy and Lexicographic Representation. - Sánchez, José Antonio Jódar (Lexikos, 2014)
Review of Sylwia Wojciechowska. Conceptual Metonymy and Lexicographic Representation.